Exposure to organophosphate ester flame retardants and plasticizers and associations with preeclampsia and blood pressure in pregnancy - Lueth, Amir J.; Bommarito, Paige A.; Stevens, Danielle R.; Welch, Barrett M.; Cantonwine, David E.; Ospina, Maria; Calafat, Antonia M.; Meeker, John D.; McElrath, Thomas F.; Ferguson, Kelly K. (Environmental research, 2024)
Organophosphate esters (OPEs), flame retardants and plasticizers found widely in consumer products, may impact vascularization processes in pregnancy. Yet, the association between maternal exposure to OPEs and both preeclampsia and blood pressure during pregnancy remains understudied. Within the LIFECODES Fetal Growth Study (N = 900), we quantified 8 OPE metabolites from maternal urine collected at up to 3 time points during pregnancy and created within-subject geometric means. Outcomes included diagnosis of preeclampsia and longitudinal systolic (SBP) and diastolic (DBP) blood pressure measurements (mean = 14 per participant). Cox proportional hazards models were used to estimate associations between OPE metabolites and preeclampsia. Associations between average OPE metabolite concentrations and repeated blood pressure measurements were estimated using generalized estimating equations. Five OPE metabolites were detected in at least 60% of samples; 3 metabolites detected less frequently (5–39%) were examined in an exploratory analysis as ever vs. never detectable in pregnancy. There were 46 cases of preeclampsia in our study population. Associations between OPE metabolites and preeclampsia were null. We noted several divergent associations between OPE metabolites and longitudinal blood pressure measurements. An interquartile range (IQR) difference in average bis(2-chloroethyl) phosphate concentrations was associated with a decrease in SBP (−0.81 mmHg, 95% confidence interval [CI]: −1.62, 0.00), and, conversely, bis(1-chloro-2-propyl) phosphate was associated with a slight increase in SBP (0.94 mmHg, 95% CI: 0.28, 1.61). We also noted a decrease in SBP in association with several metabolites with low detection frequency. We observed null associations between OPE metabolites and preeclampsia, but some positive and some inverse associations with blood pressure in pregnancy. While our study was well-designed to assess associations with blood pressure, future studies with a larger number of preeclampsia cases may be better poised to investigate the association between OPE metabolites and phenotypes of this heterogenous hypertensive disorder of pregnancy. •Eight OPE metabolites were measured from maternal urine at up to 3 time points during pregnancy.•Longitudinal systolic (SBP), and diastolic (DBP) blood pressure measurements (mean = 14 per participant).•No significant associations between OPE metabolites and preeclampsia.•Positive associations between BCIPP and blood pressure, and inverse associations for BCEP.•Decrease in SBP noted with several metabolites with low detection frequency.